Adherence inhibition of enteric pathogens to epithelial cells by bovine colostrum fractions. (January 2015) - Maldonado-Gomez, Maria X.; Lee, Hyeyoung; Barile, Daniela; Lu, Mei; Hutkins, Robert W.
Abstract: To initiate colonization, microbial pathogens express adhesins that recognize and adhere to host tissue cells. One strategy for inhibiting adherence relies on the presence of molecules that mimic epithelial receptor sites. In this study, in vitro experiments using HEp-2 cells were performed to assess the anti-adherence properties of bovine colostrum fractions against enteropathogenic Escherichia coli, Cronobacter sakazakii, and Salmonella enterica serovar Typhymurium. The results showed that protein-reduced colostrum significantly inhibited binding (from 68 to 99%) of all three pathogens to tissue culture cells. Ultrafiltration (<10, 000 Da) and nanofiltration (<1000 Da) permeates were also effective, with the ultrafiltration permeate having the broadest activity. In contrast, the nanofiltration retentate was less effective since it inhibited only Salmonella . Mass spectrometry revealed minor differences in the oligosaccharide profile, with the acidic oligosaccharides being the predominant species. This study provides evidence that bovine colostrum contains a heterogeneous mixture of anti-adherence components.